Taxonomic Revision of Dolichandra (Bignonieae, Bignoniaceae) - Fonseca, Luiz Henrique M.; Cabral, Simone Miranda; Agra, Maria De Fatima; Lohmann, Lúcia G. (Phytotaxa, 2017)
Dolichandra Cham. emend. L.G.Lohmann is a genus of Neotropical lianas in tribe Bignonieae (Bignoniaceae) that comprises nine species. It is centered in Paraguay, southern Brazil and northeastern Argentina, where six species occur and three are endemic. Species of Dolichandra are generally climbers of dry and wet lowland forests, also growing in swamps and gallery forest formations. The genus is characterized by four main synapomorphies: (i) stems with multiple dissected phloem wedges in cross-section, (ii) trifid and uncate tendrils, (iii) psilate and 3-colpate pollen, and (iv) capsules with four lines of dehiscense. Other features of the genus are the large and membranaceous calyces, dimorphic growth with the juvenile form attaching by its uncinate tendrils, lanceolate prophylls of the axillary buds, congested-cymose inflorescences, and a lobed nectary disk. In this taxonomic revision, we present detailed descriptions for all species recognized, taxonomic and nomenclatural comments, distribution maps and information on the habitat and distribution of each species, as well as information on their conservation status (i.e., IUCN categories), and illustrations of diagnostic characters. Thirty-five names are treated as synonyms, six of which are newly proposed. More specifically, Tecoma maximiliani Mart. ex DC. is synonymized under Dolichandra unguiculata (Vell.) L.G. Lohmann, Bignonia pseudounguis Desf., Bignonia unguis-cati var. radicans DC., and Macfadyena hassleri Sprague are synonymized under Dolichandra uncata (Andrews) L.G. Lohmann, while Bignonia tweediana Lindley and Dolichandra kohautiana Presl are synonymized under Dolichandra ungui-cati (L.) L.G. Lohmann. Lectotypes are proposed for 13 species names, namely Bignonia californica Brandegee, Bignonia gracilis G. Lodd., Bignonia inflata Griseb. Bignonia tweediana Lindley, Bignonia unguis-cati var. guatemalensis K. Schum. & Loes., Bignonia unguis-cati var. serrata Bureau & K. schum., Dolichandra cynanchoides Cham., Dolichandra fenzliana Miq. Macfadyena hassleri Sprague, Parabignonia steyermarkii Sandwith, Paradolichandra chodatii var. brachycalyx , Spathodea mollis and Tecoma maximiliani Mart. ex DC.